(untitled) (Journal of Atomic and Molecular Sciences, 2011)
The three-body van der Waals dispersion coefficients Z(l_1l_2l_2) (up to l_i = 5) for the H(1s)-H(1s)-H(1s) and H(2s)-H(2s)-H(2s) systems are calculated by virtue of the dynamic polarizabilities at imaginary photon frequencies. The expression for the 2^l-pole dynamic polarizabilities of atomic hydrogen is derived by application of the integration properties of the one-dimensional radial Coulomb Green's function. The results for the H(1s)-H(1s)-H(1s) system are consistent with previous calculation in the literature, while the results for the H(2s)-H(2s)-H(2s) systems are reported for the first time, and they are the main contribution of this work.